Growth Regulation with Lactofen Does Not Affect Seed Yield of Irrigated Soybean. (1st May 2016) - Mangialardi, J. Paul; Orlowski, John M.; Lawrence, Ben H.; Bond, Jason A.; Golden, Bobby R.; Catchot, Angus; Peeples, Jimmy D.; Eubank, Thomas W.
Abstract : Soybean [ Glycine max (L.) Merr.] producers have considered the use of lactofen herbicide (2‐ethoxy‐1‐methyl‐2‐oxoethyl 5‐[2‐chloro‐4‐(trifluoromethyl)phenoxy]‐2‐nitrobenzoate) as a growth regulator part of management systems for high‐yielding soybean, believing that lactofen can reduce plant height and lodging or increase node number. Previous research on non‐irrigated soybean was largely unable to show significant benefits for lactofen applied during early vegetative growth (V1–V4) as a growth regulator. However, it is unclear how early‐season lactofen applications affect soybean growth and seed yield in high‐yielding, irrigated soybean management systems common in the midsouthern United States. The purpose of this study was to investigate the effect of early‐season lactofen application on soybean injury, stunting, plant height, node number, intercepted photosynthetically active radiation, lodging, and seed yield at multiple planting dates. Trials were established during the 2013 and 2014 growing season in Stoneville, MS. Soybean was planted at four planting dates: 15 April, 1 May, 15 May, and 1 June. Crop oil concentrate (COC) and lactofen plus COC were applied to soybean at the second trifoliate growth stage (V2). Lactofen plus COC application resulted in early‐season injury and stunting, but did not affect intercepted photosynthetically active radiation, plant height at harvest, lodging, or seed yield while, planting date affected soybean plant height, but did not affect seed yield. The findings of this study suggest that the use of lactofen as a growth regulator for irrigated soybean production in the midsouthern United States is not necessary. Core Ideas Early‐season lactofen application results in temporary injury and stunting in high‐yielding, irrigated soybean in the midsouthern United States. Early‐season lactofen application does not affect soybean seed yield in high‐yield irrigated midsouthern U.S. environments. Soybean planting date failed to affect soybean seed yield in growing seasons with above‐average precipitation.